Performance of different treatment media for passive remediation of contaminants associated with acid mine drainage - Madzin, Zafira (2018)
Mining activities have often been associated with apparent environmental quality degradation and have raised environmental concerns among public. Acid mine drainage (AMD) is typically resulted from mining activities through mineral interactions with atmospheric oxygen and water. This results in the water discharges being undesirably acidic and may contain heavy metals. Hence the need to develop inexpensive and sustainable remedial method to treat contamination is required. This study was carried out to develop a passive treatment method to treat heavy metal release from mining activities. In particular, the purpose of this study is to evaluate the performance of selected treatment media in treating AMD. The treatment media used were spent mushroom compost (SMC), limestone (LS), steel slag (SS) and ochre. The first stage of the experiment was the characterization of proposed treatment media using physicchemical parameters. Then, a series of batch and column tests were conducted to determine the effectiveness of the treatment media in single and mixed substrates treatment using physic-chemical parameters and heavy metal removal analyses. Synthetic acid mine drainage water was prepared for both batch and column experiments. In the batch test, all single substrates and mixed substrates (in four different ratios namely SM1, SM2, SM3 and SM4) were tested in anoxic condition for 5 days. Assessment on the removal efficiencies were discovered and for single substrate, both SMC and SS showed promising overall heavy metal removal efficiency of 94.6% and 96.7% (r=1.000; p<0.05), respectively. Performance of SMC was supported by its high pH value, alkalinity and total organic content, whilst SS has relatively high pH (r=0.967, p<0.01) compared to other media. As for mixed substrates, SM3 which composed of 40% SS, 30% SMC, 20% LS and 10% ochre gave the best performance in overall heavy metal removal (r= 0.999, p<0.01). This treatment ratio was then used in column experiment where continuous flow of synthetic AMD water was utilised. The column test using a treatment bioreactor was conducted in lab-scale for 30 days and the results showed noticeable performance in heavy metal removal for Fe, Cu, Pb, Zn, Al, and Mn with the overall removal percentage of 83.70% in column 1 and 99.69% in column 2. The metal fraction analysis in the column sediment indicated that metal accumulation occurs mainly through adsorption onto organic matter > Fe/Mn oxides > carbonates > exchangeable > residual fractions. The assessment for removal rate in C1 and C2 from highest to lowest metal ascending are Mn>Fe>Zn>Al>Pb. Therefore, at the end of the research, characterization of treatment media has been done to unleash its potential in treating AMD. Then, assessment of batch and column experiment were carried out to measure its physicochemical parameters and heavy metal removal and finally to measure its performance in removal efficiencies, removal rate and first order kinetics.